Kesadaran Masyarakat Membayar Pajak Bumi dan Bangunan di Desa Ayula Timur Kecamatan Bulango Selatan - Fitri Usman; Radia Hafid; Cristian Polamolo (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aimed to disclose the factors that affect public awareness and the efforts made by the Ayula Timur Village office, Bulango Selatan Sub-District, in paying land and building taxes. The data in this qualitative study were collected through interviews and documentation on eight informants (two key informants and six supporters). Based on the analysis, four factors caused the lack of public awareness in paying land and building taxes in Ayula Timur Village, Bulango Selatan Sub-District: (a) tax awareness, (b) occupation and income, (c) taxpayers' understanding of land and building tax regulations, and (d) the quality of service to taxpayers. The solutions offered to increase public awareness can be in the form of counseling carried out by village officials to increase the knowledge of the land and building taxpayers, a door-to-door process to increase togetherness at the time of collection, and distributing the Notification of Tax Due on time so that the community knows the amount of tax that must be paid.